Magmatic addition rates differentiate periods of steady-state versus flare-up magmatism in the Central Andean arc - Bertin Ugarte, Daniel André (2023)
Cordilleran arcs are built by long periods of steady-state magmatism punctuated by transient high-flux magmatic episodes or flare-ups. Such flare-ups, manifested as periods of prodigious silicic volcanism and magmatism, result from geodynamic perturbations that cause elevated rates of magma addition to the crust. Questions remain, however, about how magmatic addition rates quantitatively compare between steady-state and flare-up modes of arc magmatism, and how long after the major geodynamic perturbation the flare-up begins. Here, we compute new estimates of erupted volumes over the last 35 Myr for the 22.5–29°S segment of the Central Andes based on a new volcanic geospatial database. These yield magmatic addition rates at least an order of magnitude higher during flare-up compared to steady-state conditions. A lag time of ~8–12 Myr between ocean ridge subduction (the major geodynamic perturbation in the Central Andean arc) and the onset of flare-up conditions is estimated.